Pengaruh Rekonsiliasi Fiskal terhadap Perhitungan PPh Terhutang Pada PDAM Tirta Pakuan Bogor - Hastoni, Hastoni; Pardede, Robert Pius; Astuti, Yuni (Jurnal Ilmiah Ranggagading (JIR), 2009)
This research was carried out to find out fiscal reconciliation process and debted income tax calculation, to find out the influence of fiscal reconciliation towards debted income tax calculation, and to find out fiscal reconciliation at the firm according to fiscal stipulation. The method used at this research is descriptive-explorative method. The result of this research shows that PDAM Tirta Pakuan Kota Bogor has conducted commercial balance sheet, so the firm has to make fiscal reconciliation. Taxed income imposed on PDAM Tirta Pakuan Kota Bogor is in the amount of Rp. 10.426.625.610,00 in one year. After the taxed income has been known, it can be multiplied by tax rate as written on article 17/UU PPh/2000 and it can be found out that the debted tax or the tax that must be paid by PDAM Tirta Pakuan Kota Bogor is in the amount of Rp. 365.579.030,00. Therefore, it can be concluded that the reduction result of debted income tax at PDAM Tirta Pakuan Kota Bogor at the end of the tax year, with tax credit in the relevant year, result in debted income tax is higher than the amount of tax credit, that is as high as Rp. 365.579.030,00. Key Words : Fiscal Reconciliation; Debted Income Tax